The Influence of Social Media Engagement on Spotify Users from Generation Z and Alpha: Examining the Moderating Role of FOMO - Wimboadi, Rachmad Dessardi; Bharata, Wira; Nurrohman, Rosyid; Hakim, Ahmad Firman (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
This study investigates the influence of social media engagement on trust and customer satisfaction, as well as how these factors affect repurchase intention among Spotify users from Generation Z and Generation Alpha. It also explores the moderating role of Fear of Missing Out (FOMO) in those relationships. Using a quantitative approach, data were collected from 238 respondents through an online survey and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that social media engagement significantly increases both trust and customer satisfaction. In turn, both trust and satisfaction significantly influence users’ intention to continue using the platform. FOMO strengthens the relationship between social media engagement and trust but does not significantly moderate the relationship between engagement and satisfaction. These results suggest that emotional and social factors particularly personalized digital experiences and perceived social trends play a key role in shaping digital loyalty. The study highlights the importance for digital platforms like Spotify to focus on both social engagement and accurate personalization to maintain user satisfaction and loyalty.